The Role of Zakat in Islam on Economic Growth and Optimization of Zakat Management in the Province of Bangka Belitung Islands - Wahyu Utami, Risa; Khotimah, Ramandha (Riviera Publishing, 2025)
The role of zakat in optimizing zakat management and encouraging economic growth in the context of Islam is an important topic. Zakat is the main pillar of Islam, not only a religious obligation but also plays a role in realizing economic growth. The purpose and method of this writing uses a literature study approach that relies on various literature, journal articles to obtain research data and uses a qualitative approach because the data produced is descriptive that describes or describes how zakat management efforts in Baznas Bangka Belitung Province are managed. The results of this writing illustrate that the collection of zakat experienced by Bangka Belitung Province experienced an up-and-down process that occurred from 2015 to 2019 and experienced a decline in 2021 to 2022. Efforts made by the Bangka Belitung Provincial Government include taking a bureaucratic approach to the provincial government through the Governor's policy to instruct zakat obligations to ASN, collaborating with companies and the private sector and maximizing cooperation between Regional Apparatus Organizations (OPD) within Bangka Belitung Province. Baznas Bangka Belitung will also continue to carry out socialization in a structured, systematic and massive manner both through social media and mass media.